2019
DOI: 10.1038/s41598-019-43225-3
|View full text |Cite
|
Sign up to set email alerts
|

PulmoBind Imaging Measures Reduction of Vascular Adrenomedullin Receptor Activity with Lack of effect of Sildenafil in Pulmonary Hypertension

Abstract: Endothelial dysfunction is a core pathophysiologic process in pulmonary arterial hypertension (PAH). We developed PulmoBind (PB), a novel imaging biomarker of the pulmonary vascular endothelium. 99m Technetium ( 99m Tc)-labelled PB binds to adrenomedullin receptors (AM 1 ) densely expressed in the endothelium of alveolar capillaries. We evaluated the effect of sildenafil on AM 1 receptors activity using 99m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Ramp2 mRNA is higher than Ramp3 mRNA in the lungs [ 37 ] and kidneys [ 38 ] of rats. AM derivative PulmoBind is a molecular SPECT imaging agent distributed in the human lung and is a specific ligand for AM receptor composed of CLR and RAMP2 [ 39 ]. In RD-Ag rats, Calcrl expression showed a downward trend in the lungs and was significantly reduced in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Ramp2 mRNA is higher than Ramp3 mRNA in the lungs [ 37 ] and kidneys [ 38 ] of rats. AM derivative PulmoBind is a molecular SPECT imaging agent distributed in the human lung and is a specific ligand for AM receptor composed of CLR and RAMP2 [ 39 ]. In RD-Ag rats, Calcrl expression showed a downward trend in the lungs and was significantly reduced in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…# P < .05, significantly different from PAH-SAL; Kruskal-Wallis test followed by Dunn's multiple comparisons test vitro, and ultimately reduced RVSP with minimal effects on pulmonary vascular remodelling. Previous experimental studies (Merabet et al, 2019;Schermuly et al, 2004;Zhang et al, 2019) have shown positive effects of sildenafil on vascular remodelling in PAH models. However, these studies used higher sildenafil doses (30 and 25 mgÁkg −1 , respectively) than that used in the present study (20 mgÁkg −1 ).…”
Section: Expression Of Mrna For Tgf-β and Types I And Iii Pc In Lunmentioning
confidence: 95%
“…AM receptors are abundantly expressed in the lungs, especially in the endothelium of alveolar capillaries [ 117 , 118 ], and the lung functions as a primary site for AM clearance [ 119 , 120 ]. Additionally, the expression of AM receptors is altered under pathological conditions, such as pulmonary hypertension [ 121 ]. An interesting approach for imaging the human pulmonary vascular endothelium is by using AM receptor ligands, such as 125 I-rAM (1-50) and 99m Tc-PulmoBind, for PET and SPECT imaging [ 122 – 124 ].…”
Section: Translational Studies On Am For Cvdsmentioning
confidence: 99%